Entrepreneurship prompts institutional change in developing economies - Niklas Elert; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2020)
Entrepreneurship plays a pivotal role for institutional change and economic development in transition and developing economies. Formal and informal institutions in such countries are often sub-par, but rather than being constrained by them, entrepreneurship can often affect institutions and contribute to their evolution. We highlight three entrepreneurial responses to the institutional status quo: an abiding response, an altering response, and an evasive response. Each response can be either welfare-enhancing or welfare-reducing; more importantly, each response can affect the institutional framework of the society in which it occurs. Better knowledge of entrepreneurial responses to institutions and the context in which they occur offers a promising avenue for future research and a potential way of sustaining lasting institutional change and economic development.
Keywords: L50; M13; O31; P14; 330; Development; Entrepreneurship; Evasion; Innovation; Institutions; Regulation